The Influence of Organizational Speed on Organizational Mishaps: The Moderating Role of Dynamism - Morales-Raya, Matilde; Martin-Tapia, Inmaculada; Ortiz–de–Mandojana, Natalia (My University, 2016)
Previous studies have shown the importance of organizational speed for firms’ competitive advantage and financial performance. However, more recent studies have also demonstrated that speed can be detrimental for companies. Drawing on the managerial cognitive perspective, we argue that organizational speed can contribute to organizational mishaps. We focus on organizational speed in relation to firms’ mergers and acquisitions and strategic alliances. Based on a sample of 331 companies in the United States over the period 2003-2009, our findings suggest that organizational speed has a positive influence on firms’ mishaps. Furthermore, we found that this effect is stronger when firms operate in dynamic environments.
Keywords: Empresas - Gestión; Organizational mishaps; Industry dynamism; Organizational speed; Managerial cognitive perspective.